2009
DOI: 10.1007/s10067-009-1316-7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of TLR2, TLR4, and TLR9 in dermatomyositis and polymyositis

Abstract: The aim of this study was to investigate the expressions of Toll-like receptor (TLR) 2, TLR4, TLR9, and their correlations with the expression of cytokines that are associated with activation of CD4+ T cells and inflammation including interferon γ (IFNγ), interleukin 4 (IL4), interleukin 17 (IL17), and tumor necrosis factor α (TNFα) in muscle tissues of patients with dermatomyositis (DM) and polymyositis (PM). The expressions of TLR2, TLR4, TLR9, IFNγ, IL4, IL17, and TNFα were measured by real-time reverse tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 29 publications
3
43
1
1
Order By: Relevance
“…Increased IL-17 levels have been shown in serum, PBMCs and muscle cell-infiltrating T-cells of patients with DM (2,8,9). However, we failed to show an increase in IL-17…”
Section: Discussioncontrasting
confidence: 71%
“…Increased IL-17 levels have been shown in serum, PBMCs and muscle cell-infiltrating T-cells of patients with DM (2,8,9). However, we failed to show an increase in IL-17…”
Section: Discussioncontrasting
confidence: 71%
“…TLR signaling promotes the antigen-presenting capacity (APC) to CD4+ T cells via increasing of HLA-DR [55]. CD4+T cells are divided into Th1, Th2 and Th17 cells as charcterized by the secretion of cytokines IFNγ, IL-4, and IL-17 [56][57][58]. Activation of TLR2 might induce Th2 immune response, TLR4 induces Th1 and Th17 immune response, and TLR9 induces Th1 immune response [59][60][61][62][63][64][65][66].…”
Section: Correlation Between Tlr4 and Il-17 In Dnmentioning
confidence: 99%
“…Kim et al investigated the expression of TLR2, TLR4, and TLR9 in DM patient muscle and correlated TLR expression with the expression of cytokines such as IFN-γ, IL-4, IL-17, and TNF-α. They found that the expression levels of TLR2, TLR4, and TLR9 were significantly high in patients with DM compared with those in the controls, and the expression levels of TLR4 and TLR9 had significant positive correlations with the expressions of IFN-γ, IL-4, IL-17, and TNF-α [43]. Similarly, Brunn et al showed that TLR2, TLR4, and TLR9 mRNA transcripts and protein expression were increased in muscle tissue of DM patients [44].…”
Section: Tlrmentioning
confidence: 89%